Luteinizing Hormone Receptor Mutation (LHRN316S) Causes Abnormal Follicular Development Revealed by Follicle Single-Cell Analysis and CRISPR/Cas9 - Chen Zhang; Yongqiang Nie; Bufang Xu; Chunlan Mu; Geng G. Tian; Xiaoyong Li; Weiwei Cheng; Aijun Zhang; Dali Li; Ji Wu (Interdisciplinary Sciences: Computational Life Sciences, 2024)
Abnormal interaction between granulosa cells and oocytes causes disordered development of ovarian follicles. However, the interactions between oocytes and cumulus granulosa cells (CGs), oocytes and mural granulosa cells (MGs), and CGs and MGs remain to be fully explored. Using single-cell RNA-sequencing (scRNA-seq), we determined the transcriptional profiles of oocytes, CGs and MGs in antral follicles. Analysis of scRNA-seq data revealed that CGs may regulate follicular development through the BMP15-KITL-KIT-PI3K-ARF6 pathway with elevated expression of luteinizing hormone receptor (LHR). Because internalization of the LHR is regulated by Arf6 , we constructed LHR N316S mice by CRISPR/Cas9 to further explore mechanisms of follicular development and novel treatment strategies for female infertility. Ovaries of LHR N316S mice exhibited reduced numbers of corpora lutea and ovulation. The LHR N316S mice had a reduced rate of oocyte maturation in vitro and decreased serum progesterone levels. Mating LHR N316S female mice with ICR wild type male mice revealed that the infertility rate of LHR N316S mice was 21.4% (3/14). Litter sizes from LHR N316S mice were smaller than those from control wild type female mice. The oocytes from LHR N316S mice had an increased rate of maturation in vitro after progesterone administration in vitro. Furthermore, progesterone treated LHR N316S mice produced offspring numbers per litter equivalent to WT mice. These findings provide key insights into cellular interactions in ovarian follicles and provide important clues for infertility treatment. Graphical Abstract

Serum- and Feeder-Free Culture of Juvenile Monkey Female Germline Stem Cells and Testosterone Regulation of their Self-Renewal - Xiaoyong Li; Xiaoying Yao; Chunlan Mu; Zhaoxia Wang; Rong Hu; Yan Chang; Ji Wu (Stem Cell Reviews and Reports, 2022)